1992
DOI: 10.1017/s002211209200140x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a particle-laden round jet

Abstract: The interaction of solid particles with the temporal features of a turbulent flow has direct relevance to problems in particle and spray combustion and the processing of particulate solids. The object of the present study was to examine the behaviour of particles in a jet dominated by vortex ring structures. An axisymmetric air jet laden with 55 μm glass particles was forced axially with an acoustic speaker to organize the vortex ring structures rolling up in the free shear layer downstream of the nozzle exit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(117 citation statements)
references
References 7 publications
7
107
1
2
Order By: Relevance
“…They traced the particles backwards in time and found that the most highly dispersed particles originated from inclined narrow bands within the braid regions. Their results also support previous findings by several of the above investigators, as well as by Wen et al (1992), Longmire & Eaton (1992) (for a jet), Kiger & Lasheras (1995, confirming the existence of particle concentration 'streaks' forming in braid regions between spanwise vortices (see also Crowe, Troutt & Chung 1995). In a related issue, Kiger & Lasheras (1995) found that the vortex pairing process has a homogenizing effect on the particle distribution.…”
Section: Introductionsupporting
confidence: 88%
“…They traced the particles backwards in time and found that the most highly dispersed particles originated from inclined narrow bands within the braid regions. Their results also support previous findings by several of the above investigators, as well as by Wen et al (1992), Longmire & Eaton (1992) (for a jet), Kiger & Lasheras (1995, confirming the existence of particle concentration 'streaks' forming in braid regions between spanwise vortices (see also Crowe, Troutt & Chung 1995). In a related issue, Kiger & Lasheras (1995) found that the vortex pairing process has a homogenizing effect on the particle distribution.…”
Section: Introductionsupporting
confidence: 88%
“…Experimental evidence for these preferential-concentration effects has been reported in earlier work (see for instance Longmire & Eaton 1992). In this scenario, the droplets cross the mixing layer to vaporize on the other side surrounded by hot air.…”
Section: Droplet Dispersion and Ignition In Turbulent Mixing Layersmentioning
confidence: 54%
“…2) the parameter controlling the overall dispersion characteristics in particle-laden turbulent mixing layers (Longmire & Eaton 1992). Different values of St are associated with different regimes of droplet dispersion, as depicted in figure 2 (a-c).…”
Section: Droplet Dispersion and Ignition In Turbulent Mixing Layersmentioning
confidence: 99%
“…In other shear dominated flows particle centrifuging was also found. For example Longmire & Eaton (1992) used phase-locked digital imaging to measure the spatial distribution of particle number density in a pulsed jet laden with glass beads. They found that the instantaneous number density, integrated radially over the jet, had maximum values up to three times larger than the minimum values.…”
Section: Introductionmentioning
confidence: 99%